The Influence of Government Expenditure, Investment and Number of Workers on Regional Economic Growth in the Perspective of Regional Islamic Economics in South Sumatra (Panel Data Analysis 2016-2024) - mar'uf, Maryana Ulfa; Is Susanto (International Journal of Economics (IJEC), 2025)
This study aims to analyze the impact of government spending, investment, and labor force on regional economic growth in the South Sumatra Region (Sumbagsel) from the perspective of Islamic economics over the period 2016–2024. The study employs a quantitative approach using a Fixed Effect panel data regression model covering 25 districts/cities across three provinces: South Sumatra, Bangka Belitung, and Lampung. The findings reveal that all three independent variables have a positive and statistically significant effect on regional economic growth. Foreign direct investment (FDI) exerts the most substantial impact compared to government spending and domestic investment, while the labor force contributes the least, indicating the urgent need to improve labor quality. From the Islamic economic viewpoint, the pattern of regional economic growth has not yet fully reflected key principles such as equitable income distribution, environmental sustainability, and fair business partnerships. A high Gini ratio and a low partnership index highlight the dominance of large economic actors and persistent inequality. This study recommends reforms in fiscal policy, strengthening Islamic financial institutions, and promoting halal-based economic sectors as long-term strategies. Policy implications are directed toward implementing maqashid sharia values ​​in development planning to achieve economic growth that is not only inclusive and sustainable but also aligned with Islamic moral and ethical standards